LATE CARBONIFEROUS ASSEMBLAGES OF SCHWAGERINIDS (FORAMINIFERA, SCHWAGERINIDA) IN TWO TYPES OF ORGANOGENIC STRUCTURES OF THE CENTRAL URALS - Vilesov A.P. (My University, 2002)
Two types of organogenic structures of the Central Uralian Melekhov Horizon (Gzhelian Stage, Upper Carboniferous) contain essentially different schwagerinid assemblages. Owing to the diversity of its surface biotopes, the algal-palaeoaplysinal biohermal massif is characterized by a diversity of genera and ecological groups (nine and three, respectively). The biostromal palaeoaplysinal massif contains a less diverse schwagerinid assemblage (five genera and one ecological group), which formed in uniform biotic and abiotic environments of the massif's smooth surface.
Keywords: Carboniferous; Paleozoic::Carboniferous; Палеозой::Каменноугольная